Clinical And Angiographic Characteristics Of Left Main Coronary Artery Disease, A Retrospective Study - Jawad M. Hawas; Kassim M. J. AL Doori; Mohammed H. AL Myahi (مجلة كلية الطب, 2007)
Background : Left main coronary artery (LMCA) disease represents important and serious portion of coronary artery disease(CAD). Aim: The aim of this study is to estimate the incidence of LMCA disease among patients with CAD undergoing coronary artery angiography and to evaluate clinical characteristics of patients with LMCA disease. Methods: The study involved review of clinical notes and coronary angiography of 1020 patients with CAD in Ibin Al Bitar hospital for cardiac surgery between April and September 2004.This review included evaluation of electrocardiogram (ECG), echocardiogram(ECHO), ECG exercise test (EET) and coronary angiography. Results: Among 56 patients proved to have left main coronary artery (LMCA) disease,40 patients had complete data available which were studied. Mean age of patients with LMCA disease was 60 ± 8.07 years, 82% of them were males, 62% were smokers, 40% were diabetics and 55% were hypertensive. In this group 62.5% of patients with LMCA disease presented as acute coronary syndrome (ACS) and 37.5% as chronic stable angina (CSA),normal left ventricular (LV) function was found in 75% of patients and 40% have normal electrocardiogram (ECG). Patients with LMCA disease who have distal involvement represent 75%,15% have diffusely diseased LMCA, right coronary artery (RCA) was involved in 80% of patients and those with RCA involvement were more commonly presented with ACS (78%), while those without RCA involvement presented more as CSA. Those patients who underwent ECG exercise test had poor functional Capacity, with mean  exercise duration of 3.7 ± 2.3 minutes and mean metabolic equivalents (METs) of 4.5 ± 2.46. The tests were positive in 76.9% of patients inconclusive in the rest but no negative tests were recorded. No significant differences were observed between those patients with ACS and those with CSA in regard to patients' characteristics. Conclusion: LMCA disease is not uncommon among those with CAD, it occurs in patients with multiple cardiovascular risk factors. Patients with LMCA disease usually have poor functional capacity and their ETTs are commonly positive and of high risk score. Involvements of right coronary artery (RCA) in addition to LMCA render the patients more unstable.